Disability Prevention Program Improves Life‐Space and Falls Efficacy: A Randomized Controlled Trial. Issue 1 (20th September 2020) - Liu, Minhui; Xue, Qian‐Li; Gitlin, Laura N.; Wolff, Jennifer L.; Guralnik, Jack; Leff, Bruce; Szanton, Sarah L.
Abstract : OBJECTIVES: To evaluate the effects of a home‐based disability prevention program on life‐space and falls efficacy among low‐income older adults. DESIGN: Single‐blind two‐arm randomized controlled trial. SETTING: Participants' homes. PARTICIPANTS: Participants were low‐income cognitively intact older adults (≥65 years old) with restricted daily activities. Our analytic sample for life‐space (n = 194) and falls efficacy (n = 233) varied as the life‐space measure was introduced 4 months after the trial began. INTERVENTION: Up to six 1‐hour home visits with an occupational therapist; up to four 1‐hour home visits with a registered nurse; and up to 1, 300 worth of home repairs, modifications, and assistive devices with a handyman, during a course of 4 months. MEASUREMENTS: Life‐space was measured by the Homebound Mobility Assessment; falls efficacy was measured using the 10‐item Tinetti Falls Efficacy Scale at baseline and 5 months. RESULTS: Participants were on average 75 years old, predominantly Black (86%) and female (85%–86%). Compared with participants in the control group, participants receiving the intervention were more likely to have improved versus decreased life‐space in areas of bathroom (adjusted odds ratio (OR) = 3.95; 95% confidence interval (CI) = 1.20–12.97), front or back porch, patio, or deck (adjusted OR = 2.67; 95% CI = 1.05–6.79), stairs (adjusted OR = 4.09; 95% CI = 1.34–12.48), leaving the house for any reason other than for health care (adjusted OR = 2.40; 95% CI = 1.01–5.73), and overall life‐space (adjusted OR = 2.15; 95% CI = 1.10–4.19). Participants who received the intervention also had an 11% improvement in falls efficacy in performing daily activities (exponentiated coefficient = 1.12; 95% CI = 1.04–1.21). CONCLUSION: Life‐space and falls efficacy were improved through a multicomponent, person‐directed, home‐based disability prevention intervention. Findings suggest that this intervention should be translated into different settings to promote independent aging.